High Antioxidant Activity Facilitates Maintenance of Cell Division in Leaves of Drought Tolerant Maize Hybrids - Avramova, Viktoriya; AbdElgawad, Hamada; Vasileva, Ivanina; Petrova, Alexandra S.; Holek, Anna; Mariën, Joachim; Asard, Han; Beemster, Gerrit T. S. (Frontiers in Plant Science, 2017)
We studied the impact of drought on growth regulation in leaves of thirteen maize varieties with different drought sensitivity and geographic origins (Western Europe, Egypt, South Africa) and the inbred line B73. Combining kinematic analysis of the maize leaf growth zone with biochemical measurements at a high spatial resolution allowed us to examine the correlation between the regulation of the cellular processes cell division and elongation, and the molecular redox-regulation in response to drought. Moreover, we demonstrated differences in the response of the maize lines to mild and severe levels of water deficit. Kinematic analysis indicated that drought tolerant lines experienced less impact on leaf elongation rate due to a smaller reduction of cell production, which, in turn, was due to a smaller decrease of meristem size and number of cells in the leaf meristem. Clear differences in growth responses between the groups of lines with different geographic origin were observed in response to drought. The difference in drought tolerance between the Egyptian hybrids was significantly larger than between the European and South-African hybrids. Through biochemical analyses, we investigated whether antioxidant activity in the growth zone, contributes to the drought sensitivity differences. We used a hierarchical clustering to visualize the patterns of lipid peroxidation, H2O2 and antioxidant concentrations, and enzyme activities throughout the growth zone, in response to stress. The results showed that the lines with different geographic region used different molecular strategies to cope with the stress, with the Egyptian hybrids responding more at the metabolite level and African and the European hybrids at the enzyme level. However, drought tolerance correlated with both, higher antioxidant levels throughout the growth zone and higher activities of the redox-regulating enzymes CAT, POX, APX, and GR specifically in leaf meristems. These findings provide evidence for a link between antioxidant regulation in the leaf meristem, cell division and drought tolerance.